Are the Therapeutic Effects of Huangqi (Astragalus membranaceus) on Diabetic Nephropathy Correlated with Its Regulation of Macrophage iNOS Activity? - Hui Liao; Ling Hu; Xingnuo Cheng; Xiaocheng Wang; Jiarui Li; Linda Banbury; Rongshan Li (Journal of Immunology Research)
Objective. To investigate the correlation between the clinical effects of Huangqi (Astragalus membranaceus) on different stages of diabetic nephropathy (DN) and the pharmacological effect of Huangqi on the activity of inducible nitric oxide synthase (iNOS) in macrophages in different states. Methods. The PubMed, China National Knowledge Infrastructure, and Wanfang databases were searched. Clinical data was sourced from papers on treatment of different stages of DN with Huangqi, and pharmacological data was from papers on the effects of Huangqi on the iNOS activity of macrophages in a resting or an activated state. Results. Meta-analysis of Huangqi injections on stages III and III-IV DN and randomized controlled trials on other stages showed that Huangqi had therapeutic effects on different stages of DN and on macrophages in different states: inducing normal macrophages in a resting state to generate nitric oxide (NO), tumor necrosis factor-α, and so forth upon iNOS activation; inhibiting NO generation by normal lipopolysaccharide- (LPS-) activated macrophages; and enhancing NO generation by LPS-induced macrophages from patients with renal failure. Conclusions. Huangqi can regulate iNOS activity of macrophages in different states in vitro. These biphasic or antagonistic effects may explain why Huangqi can be used to treat different stages of DN.